Argumentative Strategies and Stylistic Devices - van Haaften, Ton (Informal Logic, 2019)
The extended pragma-dialectical argumentation theory assumes that people engaged in argumentative discourse manoeuvre strategically. In argumentative reality, the strategic manoeuvring is often carried out according to an argumentative strategy. Language users make an effort to present their strategic manoeuvres in a specific way and the analysis of the stylistic choices in actual argumentative discourse is the most important basis for identification and analysis of argumentative strategies. In this article, it is shown what requirements must be satisfied by a systematic stylistic analysis of argumentative discourse, and the results of such an analysis are illustrated by means of a case study.